2006
DOI: 10.1638/04-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Szulgai Infection in a Captive Population of African Clawed Frogs (Xenopus Tropicalis)

Abstract: A colony of captive Xenopus tropicalis became infected with Mycobacterium szulgai. Clinical signs, when observed, were lethargy, weight loss, and emaciation. Visceral granulomas were common findings at laparoscopy and necropsy. The diagnosis of mycobacteriosis was based on histologic appearance and Ziehl-Neelsen staining of tissues. The identification of M. szulgai organisms was based on comparison of the 16S rRNA gene sequence with several GenBank databases. There have been no reports of this mycobacterial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 9 publications
(7 reference statements)
1
9
0
1
Order By: Relevance
“…Granulomatous inflammation with the presences of epi thelioid macrophages, multinucleated giant cells, and intralesional acid-fast positive bacilli is a consistent finding in these studies (Ramakrishnan et al 1997, Green et al 2000, Trott et al 2004, Chai et al 2006, Ferreira et al 2006, Sánchez-Morgado et al 2009, Fremont-Rahl et al 2011, Haridy et al 2014. Previous in vitro studies have suggested that salamanders may have a weak adaptive im mune response compared to Xenopus spp.…”
Section: Non-granulomatous Mycobacteriosis In 14 Hongsupporting
confidence: 56%
See 2 more Smart Citations
“…Granulomatous inflammation with the presences of epi thelioid macrophages, multinucleated giant cells, and intralesional acid-fast positive bacilli is a consistent finding in these studies (Ramakrishnan et al 1997, Green et al 2000, Trott et al 2004, Chai et al 2006, Ferreira et al 2006, Sánchez-Morgado et al 2009, Fremont-Rahl et al 2011, Haridy et al 2014. Previous in vitro studies have suggested that salamanders may have a weak adaptive im mune response compared to Xenopus spp.…”
Section: Non-granulomatous Mycobacteriosis In 14 Hongsupporting
confidence: 56%
“…To our knowledge, mycobacteriosis has not been reported in salamanders, but has been reported in other amphibians, including M. chelonae in South African clawed frogs Xenopus laevis (Green et al 2000); M. gordonae, M. liflandii, and M. szulgai in African clawed frogs Xenopus tropicalis (Chai et al 2006, Sánchez-Morgado et al 2009, Fremont-Rahl et al 2011; and M. marinum in bullfrogs Rana catesbeiana, Japanese forest green tree frogs Rhacophorus arboreus, and leopard frogs Rana pipiens (Ramakrishnan et al 1997, Ferreira et al 2006, Haridy et al 2014. Granulomatous inflammation with the presences of epi thelioid macrophages, multinucleated giant cells, and intralesional acid-fast positive bacilli is a consistent finding in these studies (Ramakrishnan et al 1997, Green et al 2000, Trott et al 2004, Chai et al 2006, Ferreira et al 2006, Sánchez-Morgado et al 2009, Fremont-Rahl et al 2011, Haridy et al 2014.…”
Section: Non-granulomatous Mycobacteriosis In 14 Hongmentioning
confidence: 83%
See 1 more Smart Citation
“…Multiple species of NTM have been isolated from frogs, including M. marinum , 9,25 Mycobacterium chelonae , 15 Mycobacterium gordonae , 28 Mycobacterium szulgai , 7 Mycobacterium xenopi , 29 and Mycobacterium liflandii. 12,34 M. liflandii was first isolated in a 2001 outbreak of mycobacteriosis in a colony of X.…”
mentioning
confidence: 99%
“…Western blot analysis was useful in the case of the Addax to differentiate it from M. bovis. Mycobacterium szulgai was recently implicated as the cause of osteoarthritis and pneumonia in African elephants (C. Lacasse et al , 2007), but could also create severe liver lesions in amphibians (Chai et al , 2006) and pneumonia in crocodiles (Roh et al , 2010).…”
Section: Ntmmentioning
confidence: 99%